Digital competencies and the use and creation of resources in university students in the field of Communications and Philology in Antioquia - Forero-Arango, Ximena; Juan Felipe, Juan Felipe (Rastros Rostros, 2025)
This paper addresses the attitudes and perceptions of undergraduate students from the Faculty of Communications and Philology at the University of Antioquia (Colombia) regarding their digital competencies and resource creation during the emergency remote education caused by the 2021 pandemic and their transition to traditional in-person education. This investigation aimed to identify these attitudes and perceptions, as well as the roles that students played in their educational process during the lockdown. This research is design-based and was conducted from a constructivist-interpretive paradigm with a qualitative approach. The main instrument was 15 semi-structured interviews with students from five undergraduate programs located in Medellín and various regions of the department of Antioquia. It corresponds to the second phase of a broader project developed at the Educational Technologies and Digital Culture Laboratory of the aforementioned academic unit, which follows an initial exploration of undergraduate teachers’ perceptions. The results of this research reveal greater digital competencies and a more creative and flexible use of resources and tools by the students, compared to a traditional teaching staff that was less prepared to adapt to the new technologies required by emergency remote education.